Bank profitability, leverage constraints, and risk-taking - Martynova, Natalya; Ratnovski, Lev; Vlahu, Razvan (Journal of Financial Intermediation, 2020)
Traditional theory suggests that higher bank profitability (or franchise value) dissuades bank risk-taking. We highlight an opposite effect: higher profitability loosens bank borrowing constraints. This enables profitable banks to take risk on a larger scale, inducing risk-taking. This effect is more pronounced when bank leverage constraints are looser, or when new investments can be financed with senior funding (such as repos). The model’s predictions are consistent with some notable cross-sectional patterns of bank risk-taking in the run-up to the 2008 crisis.